Guidelines for Addressing Problems of Operative Criminal prevention and Suppression of Police Officers: Case Study of Pa Mok Police Station in Angthong Province - Buri , Theerapat; Hombunma , Pannathorn (Journal of Dhamma for Life, 2025)
The purposes of this research were to: 1) study addressing problems of operative criminal prevention and suppression of police officers: case study of Pa Mok police station in Angthong province; 2) study guidelines for addressing problems of operative criminal prevention and suppression of police officers: case study of Pa Mok police station in Angthong province. The population is 60 police officers who perform crime prevention and suppression duties at Pa Mok Police Station, Pa Mok District, Ang Thong Province. The research instrument is a questionnaire on problem-solving guidelines for crime prevention and suppression of police officers: A case study of Pa Mok Police Station, Ang Thong Province, with an overall reliability value of 0.97 The statistics used for data analysis include frequency, percentage, mean, and standard deviation. The results of the research found that: 1) The overall problems in the performance of duties in crime prevention and suppression of police officers at Pa Mok Police Station, Ang Thong Province, were at a high level. The highest average value was budget, followed by management, and the lowest average value was equipment and materials used in performing duties; and 2) solutions to the problems in the performance of duties in crime prevention and suppression of police officers at Pa Mok Police Station, Ang Thong Province, were at a high level. The highest average value was equipment and materials used in performing duties, followed by personnel, and the lowest average value was budget.